Comparison of hydration and nutritional status between young and elderly hemodialysis patients through bioimpedance analysis - Lee JE (Dove Medical Press, 2015)
Jung Eun Lee,1,2 In Young Jo,3 Song Mi Lee,3 Woo Jeong Kim,3 Hoon Young Choi,2,4 Sung Kyu Ha,4 Hyung Jong Kim,5 Hyeong Cheon Park2,4 1Department of Internal Medicine, Yongin Severance Hospital, Yonsei University College of Medicine, 2Severance Institute for Vascular and Metabolic Research, Yonsei University College of Medicine, 3Department of Nutrition Services, Gangnam Severance Hospital, 4Department of Internal Medicine, Gangnam Severance Hospital, Yonsei University College of Medicine, Seoul, 5Department of Internal Medicine, CHA Bundang Medical Center, CHA University, Seongnam, Korea Background: The number of elderly people on dialysis is increasing rapidly. Fluid overload and malnutrition status are serious problems in elderly dialysis patients. We aimed to compare the hydration and nutritional status through bioimpedance analysis (BIA) between young and elderly hemodialysis (HD) patients and to analyze risk factors related to fluid overload and malnutrition status in these patients.Method: We conducted a cross-sectional study, in which 82 HD (males 42, mean age 58.7±12.9 years) patients were enrolled. We collected different types of data: laboratory data, such as serum creatinine, albumin, total iron-binding capacity, hemoglobin, total cholesterol; anthropometric data, such as hand grip strength (HGS); BIA data, such as intracellular water, skeletal muscle mass, body cell mass, bone mineral content, phase angle (PhA), extra cellular water (ECW)/total body water (TBW) ratio; and malnutrition-inflammation score (MIS), which is a traditional nutritional parameter for dialysis patients. All patients were stratified into two groups according to their age: young (<65 years [n=54]) and elderly (≥65 years [n=28]).Results: Total iron-binding capacity and HGS were significantly lower in elderly HD patients than in young HD patients (198.9±35.6 vs 221.4±52.1 mcg/dL; and 22.4±10.3 vs 36.4±23.2 kg, respectively) (P<0.05). Also, intracellular water and PhA measured by BIA were significantly lower (18.3±4.0 vs 20.3±4.2 L [P=0.043]; and 4.0±1.0 vs 4.9±1.2° [P=0.002], respectively), and ECW/TBW were higher in elderly HD patients (0.40±0.01 vs 0.39±0.01 [P=0.001]). ECW/TBW was positively associated with age (P<0.001) and the presence of diabetes (P<0.001) and was negatively associated with sex (P=0.001), albumin (P<0.001), urine volume (P=0.042), HGS (P<0.001), and PhA by BIA (P<0.001). MIS was negatively related to sex (P=0.001), albumin (P<0.001), HGS (P=0.001), and PhA (P<0.001) in HD patients. On multivariate analysis, older age (P=0.031), the presence of diabetes (P=0.035), and decreased PhA (P<0.001) were independent risk factors for increased ECW/TBW, representative of fluid overload status, whereas only decreased PhA (P=0.008) was a significant factor for MIS, representative of malnutrition status in these HD patients.Conclusion: We found that fluid overload and malnutrition status were more common in elderly HD patients compared with young HD patients. PhA was a significant independent factor in fluid overload status and malnutrition in these HD patients. Thus, our results indicated that PhA assessed by BIA might be a clinically useful method for assessing nutritional and hydration status in elderly HD patients. Keywords: fluid overload, malnutrition, hemodialysis, elderly patients, body compositionA Letter to the Editor has been received and published for this article.